2007
DOI: 10.1002/mabi.200700017
|View full text |Cite
|
Sign up to set email alerts
|

All‐Dry Synthesis and Coating of Methacrylic Acid Copolymers for Controlled Release

Abstract: Initiated chemical vapor deposition (iCVD) is presented as an all-dry synthesis and coating method for applying methacrylic acid copolymers as pH-responsive controlled release layers. iCVD combines the strengths of liquid-phase chemical synthesis with a precision solvent-free chemical vapor deposition environment. Copolymers of methacrylic acid and ethyl acrylate were confirmed by a systematic shift in the carbonyl bond stretching mode with a shift in the comonomer ratio within the copolymer and by the ability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
62
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(69 citation statements)
references
References 15 publications
(15 reference statements)
2
62
0
Order By: Relevance
“…The ability to dynamically alter surface properties is useful in a wide range of applications including biosensors, cell culture, microfluidics, and tissue engineering. The response of the surface can depend on externally applied stimuli, such light,150, 151, 152 temperature,87 or pH 153, 154, 155. The high degree of organic functional group retention by the iCVD synthesis method is essential for achieving the responsiveness.…”
Section: Responsive Icvd Surfaces and Devicesmentioning
confidence: 99%
See 2 more Smart Citations
“…The ability to dynamically alter surface properties is useful in a wide range of applications including biosensors, cell culture, microfluidics, and tissue engineering. The response of the surface can depend on externally applied stimuli, such light,150, 151, 152 temperature,87 or pH 153, 154, 155. The high degree of organic functional group retention by the iCVD synthesis method is essential for achieving the responsiveness.…”
Section: Responsive Icvd Surfaces and Devicesmentioning
confidence: 99%
“…pH‐responsive iCVD films have been incorporated into a variety of controlled release applications. Methacrylic acid (MAA)‐containing iCVD copolymers have been used as enteric coatings for pharmaceuticals 153. The benign reaction conditions inherent to the iCVD process make it an ideal method for coating thermally‐sensitive drugs.…”
Section: Responsive Icvd Surfaces and Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies reported that low loading efficiency and burst release were observed in microcapsules, which indicates that it is challenging to regulate the release rate of G-Rg3 in order to maintain suitable drug concentration within a therapeutic window for enough exposure time [12][15]. The main formulation of G-Rg3 medications is a mixture suspension of G-Rg3 and physiological saline [16], [17].…”
Section: Introductionmentioning
confidence: 99%
“…[24-27] We have already described in a previous paper the use of iCVD to produce 2-hydroxymethyl methacrylate (HEMA) based hydrogels with tunable swelling properties depending on the amount of incorporated crosslinking agent. [18] Also we have described the use of pentafluophenyl methacrylate (PFM) as reactive monomer for attaching biomolecules through nucleophilic substitution.…”
Section: Introductionmentioning
confidence: 99%